(Lip)stick it to the man: how YouTube beauty videos can empower women - Marshall-McKelvey, Kira, author (Colorado State University. Libraries, 2017)
“(Lip)stick it to the Man: How YouTube Beauty Videos can Empower Women” explores the tensions between traditional notions of feminism and beauty videos. My project seeks to identify ways beauty gurus use feminist narrative and invitational rhetoric in order to empower their target audiences, and to challenge limited notions of feminism. In using close textual analysis of two popular beauty gurus’ videos, I code for inclusive rhetoric and storytelling that aligns with contemporary feminism. My findings about the agentive role viewers have in shaping feminist discourse online point to future studies that focus on audience-rhetor discourse.
(Lip)stick it to the man: feminist rhetorical moves on YouTube
Lipstick it to the man
Keywords: invitational rhetoric; collaboration; YouTube; cyberfeminism